A make vs buy truck logistics decision for grain companies - Irsik, Matthew (Kansas State University, 2017)
Grain companies in the United States face many different challenges operating in a mature industry with a rich history in agriculture. The purpose of this thesis project is to examine a solution for a grain companies operating in a geographical region with considerable competition. By focusing on differentiation in level of services offered to customers, grain companies can become more profitable. The results of this study offer a solution, which centers on supply chain logistics. The objective of this project is to examine the make vs buy decision for operating a truck and trailer for grain transportation. Determining the decision factors that influence which method is the most optimal and to provide a method of relating the costs associated with each choice. In order to make an economic decision, a Truck Cost Calculator will be created to best reflect the most realistic cost structure for owning and operating a truck and trailer in house during an average crop year for a facility in Pratt County, KS. Other decision factors that are non-economic that provide a strategic benefit to a business will also be part of the project. Using industry data and relevant variables for the cost calculator, the end result is that operating choosing to operate truck logistics in house is the most cost effective option in the make vs buy decision. The optimal choice will differ individually between businesses when a strategic approach is taken to assess whether or not logistics is a core competency in the supply chain.
Keywords: Grain; Make vs. Buy; Transportation; Logistics; Truck Cost Calculator